2020
DOI: 10.4102/phcfm.v12i1.2378
|View full text |Cite
|
Sign up to set email alerts
|

A task-sharing intervention for prepartum common mental disorders: Feasibility, acceptability and responses in a South African sample

Abstract: Background: Peripartum common mental disorders (CMD) are highly prevalent in low- and middle-income countries (LMIC) such as South Africa. With limited public mental health resources, task sharing approaches to treatment are showing promise. However, little is known about the feasibility and acceptability of, as well as responses associated with problem-solving therapy (PST) for the treatment of prepartum CMD symptoms in South African public health settings.Aim: To investigate participants’ preliminary respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…We selected a South African model of brief Problem Solving Therapy (PST) (36) as the intervention to be adapted for the Ethiopian context for several reasons. These included the problem-orientated nature of stakeholders' perceptions of Ethiopian women's psychosocial distress in primary care (26), the association of perinatal depression with impaired problem-solving and coping (27), and the simplicity and acceptability of the therapeutic model for a low literacy population (37)(38)(39)(40)(41).…”
Section: Pre-adaptation Work To Select and Model The Interventionmentioning
confidence: 99%
“…We selected a South African model of brief Problem Solving Therapy (PST) (36) as the intervention to be adapted for the Ethiopian context for several reasons. These included the problem-orientated nature of stakeholders' perceptions of Ethiopian women's psychosocial distress in primary care (26), the association of perinatal depression with impaired problem-solving and coping (27), and the simplicity and acceptability of the therapeutic model for a low literacy population (37)(38)(39)(40)(41).…”
Section: Pre-adaptation Work To Select and Model The Interventionmentioning
confidence: 99%
“…We selected a South African model of brief problemsolving therapy (PST) [36] as the intervention to be adapted for the Ethiopian context for several reasons. These included the problem-orientated nature of stakeholders' perceptions of Ethiopian women's psychosocial distress in primary care [26], the association of perinatal depression with impaired problem-solving and coping [27], and the simplicity and acceptability of the therapeutic model for a low-literacy population [37][38][39][40][41].…”
Section: Pre-adaptation Work To Select and Model The Interventionmentioning
confidence: 99%
“…The third phase is making a plan to address each group of problems, to achieve what the person considers to be the most important things in their life. In meta-analyses, PST has been found to treat depression [40,41]. PST has been found to be effective and acceptable in clinical populations with relatively low levels of education [37,38,42,43].…”
Section: The Nature Of Pstmentioning
confidence: 99%
“…Over the last decade, task sharing approaches have been increasingly explored as an option to deliver mental health services in South Africa [20]. Examples of these approaches include registered counsellors providing problem-solving therapy in the treatment of antenatal common mental disorders [21], a group-based Interpersonal Therapy intervention for depression delivered by lay HIV counsellors [22], and mental health counselling to patients with chronic disease(s) which was delivered by community health workers. [23] A study in five countries (including South Africa) found that the use of nonspecialist health workers in mental health service delivery was perceived as acceptable and feasible by stakeholders if certain conditions are met including adequate training, the provision of ongoing supportive supervision, and adequate compensation.…”
Section: Introductionmentioning
confidence: 99%